Generation on fire : voices of protest from the 1960s : an oral history - Kisseloff, Jeff (Sixties--primary documents and personal narratives, 1960-1974., 2007)
The political activism of the American counterculture during the 1960s remains a subject blighted by misconceptions and stereotypes. To many, the political thought of the 1960s is synonymous with widespread drug abuse, failed social experiments, and general irresponsibility. Despite sustained public interest, few remember that many of the freedoms and rights Americans enjoy today are the direct result of those who defiantly challenged the established order during this tumultuous period. The period frightened both mainstream and elite Americans and still does. In Generation on Fire, both well-k.